Training of Batik Making and Calculating the Cost of Production of Batik in the Kedung Aren Tourism Village, Tridadi Village, Kapanewon Sleman, Sleman Regency, Special Region of Yogyakarta - Rochmad Bayu Utomo; Hamzah Gunawan; Ratri Paramitalaksmi (Jurnal Pengabdian Masyarakat Bestari, 2023)
The purpose of implementing this PkM is to help women in the Kedung Aren Tourism Village to continue working in developing the batik industry, such as (1) Making batik motifs based on their local wisdom (2) Improving their ability to make batik with natural colors (3) Knowing the cost of production from the manufacture of one batik cloth (4) Knowing the profit derived from the sale of one batik cloth. The method used is counseling and training involving 10 participants. The results of the activity showed that there was an increase in the ecoprint group's understanding of leaves that could be used in the ecoprint process. Currently partners also have a clear organizational structure, there is an increased understanding of making batik with ecoprint techniques and service partners already have their own ecoprint production tools and available capital.